Effect of probiotics intake on constipation in children: an umbrella review - Dong, Mingyang; Wu, Yuting; Zhang, Mengzhen; Chen, Pengjun; Zhang, Zhiyang; Wang, Shu (Frontiers in Nutrition, 2023)
Based on existing systematic reviews and meta-analyse we conducted this comprehensive review to evaluate the quality, effectiveness, and bias of evidence regarding the relationship between probiotic intake and improved constipation outcomes in children. A total of nine meta-analyses and systematic reviews were extracted from 628 articles, summarizing seven effectiveness indicators and the incidence of adverse reactions in the treatment of constipation. According to the results, our study revealed that the intake of probiotics in children with FC significantly improved treatment success rate and defecation frequency, while decreased the recurrence rate of constipation. However, no significant association was detected between probiotics intake and frequency of abdominal pain, stool consistency, frequency of defecation pain, frequency of fecal incontinence of children with FC. The intake of probiotics did not increase the incidence of adverse reactions and demonstrated good safety.